Analisis Dampak Pemekaran Daerah Terhadap Kinerja Keuangan dan Pelayanan Publik - Endah Trikurniasih; Rahmi Handayani; Agus Santoso; Ahmad Soleh (Universitas Batanghari Jambi, 2019)
Decentralization is a tool to achieve one of the objectives of the state, especially providing public services. Decentralization is often called granting autonomy. The formation of autonomous regions, including through regional expansion. During the 16 years of the decentralization era, the rate of increase in DOB was very fast. In addition to the growth of new autonomous regions, transfers of central revenue to regions have also increased. Following the national phenomenon, the implementation of decentralization in Jambi Province was also marked by regional expansion. Jambi Province is one of the provinces that has significantly expanded regions. Regional expansion is deemed necessary given the development of the population and the increasing workload and work volume in each district. On that basis, I would like to carry out research related to the impact of pemekaran on financial performance and public services. This study aims to analyze the impact of regional expansion in Jambi Province on parent regions and new autonomous regions in terms of regional and public financial aspects in the post-division period. Analysis of the data in this study used qualitative and quantitative descriptive analysis. The results showed that regional expansion had a positive impact on financial performance and public services.